Bid-Ask Spreads, Volatility, Quote Revisions and Trades of Thinly Traded Futures Contracts - DING, David K. (Institutional Knowledge at Singapore Management University, 2003)
Intraday bid-ask spreads (BAS), volatility, and trading activity of thinly traded equity index futures contracts on the Singapore Exchange are investigated. Contrary to previous findings, a rather flat BAS pattern in found during the trading day. However, consistent with past findings, an increase in risk widens the spread and a higher trading activity reduces it. When trading occurs in a day, spreads are reduced. No significant difference in volatility between days with and without trades was detected. When trades occur, quote revisions increase, and it is positively related to the number of trades. An increase in the number of quote revisions increases the likelihood of a transaction, and when quotes are current, revisions that are accompanied by trades carry new information. Evidence is provided that contracts that are thinly traded may possess liquidity attributes as long as their price quotes remain current.